Pengaruh Stres Kerja, Komunikasi Internal dan Dukungan Organisasi terhadap Kinerja Pegawai pada Dinas Sosial Kabupaten Asahan - Nanda Sri Wahyuni; Aris Siregar (Sekolah Menengah Kejuruan (SMK) Pustek, 2026)
Employee performance is an important factor in achieving organizational goals, particularly in public service institutions that require effective coordination and optimal work quality. However, employee performance may be affected by several organizational factors, including excessive work stress, ineffective internal communication, and limited organizational support. Therefore, this study aims to analyze the partial and simultaneous effects of work stress, internal communication, and organizational support on employee performance. This research employed a quantitative approach with an associative research method. The respondents consisted of 63 employees selected using a saturated sampling technique. The research data were collected through the distribution of Likert-scale questionnaires. Furthermore, the data were processed using SPSS version 25 and analyzed through multiple linear regression analysis. The results of the study indicate that work stress, internal communication, and organizational support significantly affect employee performance, both partially and simultaneously. Effective communication and strong organizational support were found to improve employee performance, while excessive work stress tended to reduce work effectiveness.